2018
DOI: 10.1016/j.ajog.2017.12.229
|View full text |Cite
|
Sign up to set email alerts
|

A new customized fetal growth standard for African American women: the PRB/NICHD Detroit study

Abstract: Background The assessment of fetal growth disorders requires a standard. Current nomograms for the assessment of fetal growth in African American women have been derived either from neonatal (rather than fetal) biometry data or have not been customized for maternal ethnicity, weight, height, parity, and fetal sex. Objective We sought to 1) develop a new customized fetal growth standard for African American mothers; and 2) compare such a standard to three existing standards for the classification of fetuses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 71 publications
4
22
1
1
Order By: Relevance
“…This is in accordance with findings from other studies 29,30 that the use of the INTER-GROWTH-21st standard underestimates the proportion of SGA live births and SGA infants at risk of perinatal mortality and morbidity. Furthermore, both The Eunice Kennedy Shriver National Institute of Child Health and Human Development A study 31 that was designed to assess whether specific racial/ethnic-specific foetal growth standards were needed and the PRB/NICHD Detroit study 32 concluded that there is highly statistically significant racial/ethnic differences in foetal growth resulting in the publication of racial/ethnic-specific derived standards supporting our findings about the need of customized rather than multinational formulas.…”
Section: Growth In Singleton Foetuses Of Greek Origin 2 8 (Alexandrossupporting
confidence: 78%
“…This is in accordance with findings from other studies 29,30 that the use of the INTER-GROWTH-21st standard underestimates the proportion of SGA live births and SGA infants at risk of perinatal mortality and morbidity. Furthermore, both The Eunice Kennedy Shriver National Institute of Child Health and Human Development A study 31 that was designed to assess whether specific racial/ethnic-specific foetal growth standards were needed and the PRB/NICHD Detroit study 32 concluded that there is highly statistically significant racial/ethnic differences in foetal growth resulting in the publication of racial/ethnic-specific derived standards supporting our findings about the need of customized rather than multinational formulas.…”
Section: Growth In Singleton Foetuses Of Greek Origin 2 8 (Alexandrossupporting
confidence: 78%
“…For the PRB/NICHD standard, EFW was calculated using the three‐parameter Hadlock formula (HC, AC and FL) and corresponding customized centiles were calculated using the R package available at http://bioinformaticsprb.med.wayne.edu/software/prb-nichd-fetal-growth-standard/. Growth centiles were customized for maternal height, weight and parity, and fetal sex.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of these factors were assumed to be proportionally constant during gestation, and adjustment coefficients were estimated from birth weight data in specific populations. More recent customized standards do not rely on the proportionality assumption and allow these effects to vary among the specific centile curves.…”
Section: Introductionmentioning
confidence: 99%
“…The PRB/NICHD Detroit study included only black women living in Detroit and classified 11.6% of term black fetuses as SGA, which may be due to their inclusion of pathological pregnancies. 13 The INTERGROWTH study combined multiple racial and ethnic populations from eight countries but included only normal healthy pregnancies, creating in international standard based on the premise that there is no biological basis for variation in fetal growth by population. 14 Whether varied growth curves of different populations of fetuses is physiological or pathological remains debated.…”
Section: Discussionmentioning
confidence: 99%